Communication pattern, differentiation and satisfaction in couple relationships: validation and anaysis of these scales in Spanish samples. - Montes-Berges, Beatriz (Anales de Psicología / Annals of Psychology, 2009)
Studies about violence point out that there is a relationship between Communication Patterns, Differentiation in the Couple and with Satisfaction with the Partner, and the family violence research (Badcock, Waltz, Jacobson y Gottman, 1993; Bartle y Rosen, 1994; Cook and Frantz-Cook, 1984; Penn, 2002). However, the scales which measure these vari-ables are not available in Spanish. Hence, it was necessary to adapt and validate them. In the present work, we do it, focussing on their psycho-metric properties. Finally, we describe the correlations between these three variables, paying special attention to the relationships that emerged be-tween the different questionnaire’s subscales and the satisfaction with the couple scale.